Measuring Up: Evaluating the Impact of P/CVE Programs - Holmer, Georgia; Bauman, Peter; Araeinejad, Kateira (United States Institute of Peace, 2018)
This report considers the various conceptual and practical challenges in measuring the impact and value of programs designed to prevent and counter violent extremism (P/CVE). It examines potential solutions and emphasizes the significance of efforts to assess changes in attitudes , behaviors, and relationships. The report was developed in tandem wit h “Taking Stock: Analytic Tools for Understanding and Designing P/CVE Programs” and seeks to help advance more rigor and sustainability in P /CVE programming.